Effect of Thermotherapy on Mixed Urinary Incontinence Based on Persian Medicine: A Case Report - Laila Shirbeigi; Zahra Niktabe; Nematollah Masoudi; Malihe Tabrrai; Fatemeh Nejatbakhsh (Tehran University of Medical Sciences, 2017)
Involuntary urination called urinary incontinence, is a worldwide major health problem with enormous negative consequences. Three large categories in women urinary incontinence are: stress urinary incontinence, urge urinary incontinence and mixed urinary incontinence. The diseases mechanism is seen as the muscle dysfunction of the bladder's wall and sphincter. In Iranian Traditional Medicine literature, women urinary incontinence has two main reasons: cold and wet- temperament affecting the bladder muscle dysfunction, and relaxation of bladder sphincter. Both conditions occur due to cold-nature and humidity.We present a 53-years-old woman with chronic mixed urinary incontinence that has shown an acceptable response to simple topical heating treatments designed on the basis of Iranian Traditional Medicine to eliminate the mentioned cold and wet temperament based on relative questionnaire. After 4 weeks thermotherapy, score of disease severity improved significant. In follow of patient after 6 weeks the effect of treatment was indelible.